Kualitas Pelayanan Jasa Penerbangan PT Garuda Indonesia - Roudhotul Jannah; Hendra Sukmana (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine the quality of Garuda Indonesia's flight services. The research method is qualitative using a descriptive approach. Data collection techniques conducted by researchers through observation, interviews, and documentation techniques. Data analysis in this study uses three components, namely data reduction, data presentation, and drawing conclusions. Research Results The level of competence of employees of PT. Garuda Indonesia is very good, because before becoming an employee, you must take the training that has been provided from various sub-variables such as education level, number of years of work experience, so that the quality of service provided by PT Garuda Indonesia through employees to passengers is very satisfactory. The quality of PT Garuda Indonesia's flight services provided to passengers is very satisfying, from the waiting room facilities and equipment from ticket reservations, check-in, boarding passes to take-off and take-off processes, very concerned about passenger comfort and safety, PT Garuda Indonesia's organizational culture through hospitality Indonesian hospitality is applied in an icon that indulges the senses. Garuda Indonesia Experience is a new service concept that presents the best aspects of Indonesia to passengers. Keywords: Service Quality, Aviation Services, PT Garuda Indonesia